Successful desensitization therapy involving fluoroquinolone for the treatment of a solitary tuberculoma: A case report and literature review - WATANABE, HIDEHIRO (Mol Clin Oncol, 2016)
The patient was a 31-year-old female with no previous health problems; however, during a health checkup in 2013, a nodule (2.5 cm in diameter) was identified in the S10 area of the left lung. No clinical symptoms were apparent. Positron emission tomography/computed tomography revealed an accumulation in the same region. The patient was suspected of having lung cancer, and video-assisted thoracoscopic surgery was performed. A histopathological examination of the resected specimen revealed epithelioid granulomas accompanied by caseous necrosis in the lesion. The culture was positive for Mycobacterium tuberculosis, which led to the final diagnosis of tuberculoma. Initially, the patient underwent anti-M.tuberculosis treatment [isoniazid (INH) + rifampicin (RFP) + ethambutol (EB) + pyrazinamide (PZA)]. However, two weeks later, the development of epatic dysfunction necessitated suspension of the medication. Treatment was resumed following improvement of the hepatic function. However, this relapsed two weeks later, resulting in discontinuation of the treatment. The patient was negative for each of the four drugs in the drug-induced lymphocyte stimulation test (DLST), and drug-induced hepatotoxicity (DIH) attributable to the anti-tuberculous drugs that were administered. Therefore, desensitization therapy was initiated. EB + PZA were changed to levofloxacin (LVFX) at an initial dose of 250 mg/day (dose level increased to the maintenance dose). Subsequently, desensitization therapy with RFP and INH was applied in accordance with the Japanese Society for Tuberculosis protocol. After each drug dose level reached the maintenance dose level, the therapy was completed following administration of the drugs for the recommended duration of 6 months. There were no signs of relapse 6 months following completion of the therapy. Therefore, the patient responded well to the substitute therapy with LVFX and desensitization therapy, and the present case report provided information regarding the treatment of tuberculoma.